Impacto del uso de la plataforma digital Evea en el rendimiento académico de los estudiantes de comunicación del 8vo semestre de la Universidad Estatal de Bolívar, durante la pandemia covid-19, periodo 2023. - Paz Nuñez, Neida Anais (2024)
The State University of Bolivar is a public institution of higher education, located in the province Bolivar canton Guaranda, this institution trains competent professionals who aspire to obtain a university degree, formed by teachers trained to practice education. The objective of this study was to evaluate the impact of the use of the digital platform EVEA on the academic performance of 8th semester communication students of the State University of Bolivar during the COVID-19 pandemic in the period 2023. The study focused on the analysis of various aspects related to the use of the EVEA platform, such as accessibility, ease of use, teacher-student interaction, quality of the educational resources available and the effectiveness of the evaluation and monitoring tools. In addition, the perceptions and experiences of students when using the platform are examined, as well as the factors that may affect their academic performance. Among the most important conclusions of the research it can be highlighted that through the analysis of the data collected by surveys and the observation sheet, showed the level of adaptation and use of the EVEA digital platform of the 8th cycle students, was at a good level. Demonstrating that the platform has been adopted and used by a significant number of students after the pandemic.